PENGARUH MODEL LATIHAN LIFE KINETIK TERHADAP PENINGKATAN PERCAYA DIRI ATLET PADA CABANG OLAHRAGA KATEGORI OPEN SKILL DAN CLOSED SKILL - Mochammad Fajar Shidiq Nugraha, - (2022)
The background of this research is based on the analysis of researcher, athletes in the open skill and closed skill categories of sports are still lacking in self-confidence. The purpose of this study was to determine "the effect of the life kinetic training model on increasing the athlete's self-confidence in the open skill and closed skill categories of sports ". The research method used is an experimental research method using One Group Pre-Test Post-test Design. The data collection technique is done by giving an initial test / pre-test . Then given treatment using a life kinetic exercise model . Then given a final test / post-test . The data processing technique used in this research is the Paired Sample T-Test and the Independent Samples T-test . The samples used in this study were athletes from UKM Basketball, UKM Volleyball, UKM Aquatics and UKM Athletics UPI totaling 28 athletes consisting of 14 athletes in the open skill category and 14 athletes in the closed skill category . This research was conducted for 4 weeks and carried out for 16 meetings. The results of this study indicate that the life kinetic training model has a significant effect on increasing the confidence of athletes in the open skill and closed skill categories , and there is a difference in increasing the athlete's confidence between open skills and closed skills on the life kinetic training model .